How good is the data for tracking countries’ agricultural greenhouse gas emissions? Making use of multiple national greenhouse gas inventories - Dittmer, Kyle M.; Wollenberg, Eva; Cohen, Milo; Egler, Cecelia (Frontiers in Sustainable Food Systems, 2023)
Tracking agriculture and land-use greenhouse gas (GHG) emissions is necessary to inform global climate policy, yet UNFCCC country-reported data and three independent global databases show inconsistent estimates of countries’ emissions. Data for developing countries are particularly inconsistent, yet also collectively the largest source of emissions. The purpose of this paper is to provide transparency about available country-level emissions data for agriculture and related land use and characterize their data quality and consistency to enable better understanding of available data and tracking of climate change mitigation. We call for increased consistency of official national GHG inventory data for agriculture and transparency about the differences among scientific data sources to enable decision makers to track progress, set priorities and manage emissions.